Evaluasi Kualitas Sistem, Informasi dan Layanan Website Perguruan Tinggi sebagai Media Informasi Pemangku Kepentingan - Yulita Setiawanta; Melati Oktafiyani (Jurnal Bisnis dan Ekonomi, 2020)
This study is aim to empirically the relationship between the statement on the readiness of the forms of statements related to communication, information and information dissemination on the research results of the satisfaction of users of information systems so that an understanding can be reached between the standard statement at an optimal value with the results of this study later. The data collection used in this study is survey method. The samples were undergraduate accounting students of Dian Nuswantoro University. The sample used in this study was representativeness with the Slovin formula and simple random sampling. Multiple linear regression as a data analysis tool. The results showed that the quality of information, system quality, service quality have an effect on the user satisfaction of Accounting Department’s website of Dian Nuswantoro University.